The contribution of the alternative pathway in complement activation on cell surfaces depends on the strength of classical pathway initiation - Boer, Esther CW; Thielen, Astrid JF; Langereis, Jeroen D; Kamp, Angela; Brouwer, Mieke C; Oskam, Nienke; Jongsma, Marlieke L; Baral, April J; Spaapen, Robbert M; Zeerleder, Sacha; Vidarsson, Gestur; Rispens, Theo; et al. (Clinical & translational immunology, 2023)
Objectives The complement system is an important component of innate immunity. The alternative pathway (AP) amplification loop is considered an essential feed forward mechanism for complement activation. However, the role of the AP in classical pathway (CP) activation has only been studied in ELISA settings. Here, we investigated its contribution on physiologically relevant surfaces of human cells and bacterial pathogens and in antibody‐mediated complement activation, including in autoimmune haemolytic anaemia (AIHA) setting with autoantibodies against red blood cells (RBCs). Methods We evaluated the contribution of the AP to complement responses initiated through the CP on human RBCs by serum of AIHA patients and recombinant antibodies. Moreover, we studied complement activation on Neisseria meningitidis and Escherichia coli. The effect of the AP was examined using either AP‐depleted sera or antibodies against factor B and factor D. Results We show that the amplification loop is redundant when efficient CP activation takes place. This is independent of the presence of membrane‐bound complement regulators. The role of the AP may become significant when insufficient CP complement activation occurs, but this depends on antibody levels and (sub)class. Our data indicate that therapeutic intervention in the amplification loop will most likely not be effective to treat antibody‐mediated diseases. Conclusion The AP can be bypassed through efficient CP activation. The AP amplification loop has a role in complement activation during conditions of modest activation via the CP, when it can allow for efficient complement‐mediated killing. The alternative pathway (AP) amplification loop is considered an essential feed forward mechanism for activation of the complement system. On physiologically relevant surfaces of red blood cells and bacteria, we show that the AP can be bypassed if classical pathway (CP) activation is strong, due to high antibody levels or antibody class. The AP has a role in complement activation during low activation via the CP, when it can allow for efficient complement‐mediated killing.